Commuting behavior adaptation to flooding: An analysis of transit users’ choices in Metro Manila - Abad, Raymund Paolo B. (Animo Repository, 2020)
People are likely to adapt their everyday travel behavior when faced with adverse weather conditions like flooding. Variations in their usual travel routine often manifest in changes made in departure time, transport mode use or route taken, or cancellation of travel. The current study aims to understand how commuters in Metro Manila adjust their travel behavior in response to flooding events. Questionnaire data collected among employees demonstrate that in Metro Manila adaptation of commute behavior in response to flood events occur more often during the trip to work than during the return to home, and mostly consist of changes to the departure time. In addition, the outcomes for a series of binary logit models are consistent with the claim that whether adaptations are made to commuting behavior primarily depends on the respondent's commute and employment situation. Perceived flood characteristics sociodemographic profile and commuters’ beliefs about changes over time in the frequency of flood events all played a role but were much less weakly associated with the inclination to adapt commuting behavior. Recommendations for transit agencies and employers are derived from the analysis so that affected travelers can adapt to travel conditions during flood events without compromising commitments in the household or in the workplace. © 2019 Hong Kong Society for Transportation Studies